X-band Band-pass Frequency Selective Surface for Radome Applications - Tariq Rahim; Jiodong Xu (Institute of Advanced Engineering and Science, 2015)
A low profile multi layer miniaturized unit cell frequency selective surface (FSS) with second-order band-pass response is design. The metallic layers in the form of capacitive patches and inductive grids are separated by dielectric substrates. The non-resonant sub-wavelength unit cells with unit cell dimensions and periodicities on the order of 0.15λ. The overall thickness of approximately 0.03λ is designed which is useful at lower frequencies with long wavelengths. The FSS exhibit a stable frequency response to different angles of incidence and polarizations. The analysis and synthesis of the FSS is done using equivalent circuit method and simulated using CST microwave studio at X-band.